Application Of Responsibility Accounting Budget As Cost Control On PT. Selamat Samudra Grup Bengkulu City - Evi Harlinda; Yun Fitriano; Abdul Rahman (Penerbit Jurnal Indonesia, 2023)
The purpose of this research is to find out how the implementation of budgetary accountability accounting as a cost control at PT. Selamat Samudra Grup Bengkulu City. This research is only limited to organizational structure, budgeting, separation of controlled and uncontrolled costs, preparation of account codes, and cost reporting or accountability accounting at PT. Selamat Samudra Grup Bengkulu City. The research method used is descriptive qualitative and compares the theory used with the results of interviews with the leadership of PT. Selamat Samudra Grup Bengkulu City. From the research method, it can be concluded that PT. Selamat Samudra Grup Bengkulu City has implemented budgetary accountability accounting as a cost control well which has 84% ​​conformity with the theory used in the research. However, there are 16% discrepancies due to several factors such as inefficient work and delays in cost reporting, therefore the company must be able to correct the factors of the discrepancy.